2021
DOI: 10.4102/ajlm.v10i1.1318
|View full text |Cite
|
Sign up to set email alerts
|

In-depth investigation of turn-around time of full blood count tests requested from a clinical haematology outpatient department in Cape Town, South Africa

Abstract: Background: The performance of laboratories can be objectively assessed using the overall turn-around time (TAT). However, TAT is defined differently by the laboratory and clinicians; therefore, it is important to determine the contribution of all the different components making up the laboratory test cycle.Objective: We carried out a retrospective analysis of the TAT of full blood count tests requested from the haematology outpatient department at Tygerberg Academic Hospital in Cape Town, South Africa, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…Our results showed that most samples were processed in the laboratory within 90 minutes and the median TAT-intra laboratory was 56 minutes (IQR: 36-80 minutes). These results are similar to the studies of Mutema et al [ 13 ] and Mahdaviazad et al [ 21 ]. In contrast, Winkelman et al stated that this median time was 35 minutes for urgent hospital tests [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results showed that most samples were processed in the laboratory within 90 minutes and the median TAT-intra laboratory was 56 minutes (IQR: 36-80 minutes). These results are similar to the studies of Mutema et al [ 13 ] and Mahdaviazad et al [ 21 ]. In contrast, Winkelman et al stated that this median time was 35 minutes for urgent hospital tests [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…In order to achieve this objective, the laboratory can adopt a quality approach that consists of improving its results' turnaround time (TAT) [11]. The TAT is a crucial parameter in the clinic that reflects the performance of a laboratory and the efficiency of all the analysis processes from the pre-analytical phase to the postanalytical phase [12,13]. Currently, the Lean Six Sigma (LSS) method is the most adopted methodology by several laboratories in Europe and America and their impact has been well illustrated [11,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, a less-developed area like Africa has about 24% of the global burden of disease but only 3% of the global health personnel [ 3 ]. This irregular distribution of qualified health workers is a longstanding issue, especially in the rural areas of various countries [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%